Differential Effects of Substrate Type and Genet on Growth of Microfragments of Acropora palmata - Papke, Erin; Wallace, Bailey; Hamlyn, Sarah; Nowicki, Robert (Frontiers in Marine Science, 2021)
Global decline of coral reefs has led to a widespread adoption of asexual propagation techniques for coral restoration, whereby coral colonies are fragmented and allowed to re-grow before being returned to the reef. While this approach has become increasingly popular and successful, many questions remain regarding best practices to maximize restoration speed, efficiency, and survival. Two variables that may influence growth and survival of asexually fragmented colonies include coral genet and growth substrate. Here, we evaluate the effects of genet and substrate (commercially available ceramic vs. in-house made cement) on the survival and growth of 221 microfragments of elkhorn coral Acropora palmata over 193 days. All corals survived the experimental period, and doubled their initial size in 45 days, with an average growth of 545% over the study duration. Growth was generally linear, though the growth of some corals more closely matched logistic, logarithmic, or exponential curves. Both genet and substrate had significant effects on coral growth, though the two factors did not interact. Genet had a stronger influence on coral growth than substrate, with the fastest genet growing at 216% the rate of the slowest genet. Corals on cement substrate grew at 111.9% the rate of those grown on ceramic. This represents both a significant cost savings and elimination of logistical challenges to restoration practitioners, as the cement substrate ingredients are cheap and globally available. Our work shows that both genet and substrate should be considered when undertaking asexual restoration of Acropora palmata to maximize restoration speed and efficiency.